-
Notifications
You must be signed in to change notification settings - Fork 246
/
Copy pathProperties.agda
1189 lines (954 loc) · 48.3 KB
/
Properties.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
622
623
624
625
626
627
628
629
630
631
632
633
634
635
636
637
638
639
640
641
642
643
644
645
646
647
648
649
650
651
652
653
654
655
656
657
658
659
660
661
662
663
664
665
666
667
668
669
670
671
672
673
674
675
676
677
678
679
680
681
682
683
684
685
686
687
688
689
690
691
692
693
694
695
696
697
698
699
700
701
702
703
704
705
706
707
708
709
710
711
712
713
714
715
716
717
718
719
720
721
722
723
724
725
726
727
728
729
730
731
732
733
734
735
736
737
738
739
740
741
742
743
744
745
746
747
748
749
750
751
752
753
754
755
756
757
758
759
760
761
762
763
764
765
766
767
768
769
770
771
772
773
774
775
776
777
778
779
780
781
782
783
784
785
786
787
788
789
790
791
792
793
794
795
796
797
798
799
800
801
802
803
804
805
806
807
808
809
810
811
812
813
814
815
816
817
818
819
820
821
822
823
824
825
826
827
828
829
830
831
832
833
834
835
836
837
838
839
840
841
842
843
844
845
846
847
848
849
850
851
852
853
854
855
856
857
858
859
860
861
862
863
864
865
866
867
868
869
870
871
872
873
874
875
876
877
878
879
880
881
882
883
884
885
886
887
888
889
890
891
892
893
894
895
896
897
898
899
900
901
902
903
904
905
906
907
908
909
910
911
912
913
914
915
916
917
918
919
920
921
922
923
924
925
926
927
928
929
930
931
932
933
934
935
936
937
938
939
940
941
942
943
944
945
946
947
948
949
950
951
952
953
954
955
956
957
958
959
960
961
962
963
964
965
966
967
968
969
970
971
972
973
974
975
976
977
978
979
980
981
982
983
984
985
986
987
988
989
990
991
992
993
994
995
996
997
998
999
1000
------------------------------------------------------------------------
-- The Agda standard library
--
-- Properties related to Fin, and operations making use of these
-- properties (or other properties not available in Data.Fin)
------------------------------------------------------------------------
{-# OPTIONS --cubical-compatible --safe #-}
{-# OPTIONS --warn=noUserWarning #-} -- for deprecated _≺_ and _≻toℕ_ (issue #1726)
module Data.Fin.Properties where
open import Axiom.Extensionality.Propositional
open import Algebra.Definitions using (Involutive)
open import Effect.Applicative using (RawApplicative)
open import Effect.Functor using (RawFunctor)
open import Data.Bool.Base using (Bool; true; false; not; _∧_; _∨_)
open import Data.Empty using (⊥; ⊥-elim)
open import Data.Fin.Base
open import Data.Fin.Patterns
open import Data.Nat.Base as ℕ
using (ℕ; zero; suc; s≤s; z≤n; z<s; s<s; s<s⁻¹; _∸_; _^_)
import Data.Nat.Properties as ℕ
open import Data.Unit.Base using (⊤; tt)
open import Data.Product.Base as Product
using (∃; ∃₂; _×_; _,_; map; proj₁; proj₂; uncurry; <_,_>)
open import Data.Product.Properties using (,-injective)
open import Data.Product.Algebra using (×-cong)
open import Data.Sum.Base as Sum using (_⊎_; inj₁; inj₂; [_,_]; [_,_]′)
open import Data.Sum.Properties using ([,]-map; [,]-∘)
open import Function.Base using (_∘_; id; _$_; flip)
open import Function.Bundles using (Injection; _↣_; _⇔_; _↔_; mk⇔; mk↔ₛ′)
open import Function.Definitions using (Injective; Surjective)
open import Function.Consequences.Propositional using (contraInjective)
open import Function.Construct.Composition as Comp hiding (injective)
open import Level using (Level)
open import Relation.Binary.Definitions as B hiding (Decidable)
open import Relation.Binary.Core using (_⇒_; _Preserves_⟶_)
open import Relation.Binary.Bundles
using (Preorder; Setoid; DecSetoid; Poset; TotalOrder; DecTotalOrder; StrictPartialOrder; StrictTotalOrder)
open import Relation.Binary.Structures
using (IsDecEquivalence; IsPreorder; IsPartialOrder; IsTotalOrder; IsDecTotalOrder; IsStrictPartialOrder; IsStrictTotalOrder)
open import Relation.Binary.PropositionalEquality.Core as ≡
using (_≡_; _≢_; refl; sym; trans; cong; cong₂; subst; _≗_)
open import Relation.Binary.PropositionalEquality.Properties as ≡
using (module ≡-Reasoning)
open import Relation.Nullary.Decidable as Dec
using (Dec; _because_; yes; no; _×-dec_; _⊎-dec_; map′)
open import Relation.Nullary.Negation.Core using (¬_; contradiction)
open import Relation.Nullary.Reflects using (Reflects; invert)
open import Relation.Unary as U
using (U; Pred; Decidable; _⊆_; Satisfiable; Universal)
open import Relation.Unary.Properties using (U?)
private
variable
a : Level
A : Set a
m n o : ℕ
i j : Fin n
------------------------------------------------------------------------
-- Fin
------------------------------------------------------------------------
¬Fin0 : ¬ Fin 0
¬Fin0 ()
nonZeroIndex : Fin n → ℕ.NonZero n
nonZeroIndex {n = suc _} _ = _
------------------------------------------------------------------------
-- Bundles
0↔⊥ : Fin 0 ↔ ⊥
0↔⊥ = mk↔ₛ′ ¬Fin0 (λ ()) (λ ()) (λ ())
1↔⊤ : Fin 1 ↔ ⊤
1↔⊤ = mk↔ₛ′ (λ { 0F → tt }) (λ { tt → 0F }) (λ { tt → refl }) λ { 0F → refl }
2↔Bool : Fin 2 ↔ Bool
2↔Bool = mk↔ₛ′ (λ { 0F → false; 1F → true }) (λ { false → 0F ; true → 1F })
(λ { false → refl ; true → refl }) (λ { 0F → refl ; 1F → refl })
------------------------------------------------------------------------
-- Properties of _≡_
------------------------------------------------------------------------
0≢1+n : zero ≢ Fin.suc i
0≢1+n ()
suc-injective : Fin.suc i ≡ suc j → i ≡ j
suc-injective refl = refl
infix 4 _≟_
_≟_ : DecidableEquality (Fin n)
zero ≟ zero = yes refl
zero ≟ suc y = no λ()
suc x ≟ zero = no λ()
suc x ≟ suc y = map′ (cong suc) suc-injective (x ≟ y)
------------------------------------------------------------------------
-- Structures
≡-isDecEquivalence : IsDecEquivalence {A = Fin n} _≡_
≡-isDecEquivalence = record
{ isEquivalence = ≡.isEquivalence
; _≟_ = _≟_
}
------------------------------------------------------------------------
-- Bundles
≡-preorder : ℕ → Preorder _ _ _
≡-preorder n = ≡.preorder (Fin n)
≡-setoid : ℕ → Setoid _ _
≡-setoid n = ≡.setoid (Fin n)
≡-decSetoid : ℕ → DecSetoid _ _
≡-decSetoid n = record
{ isDecEquivalence = ≡-isDecEquivalence {n}
}
------------------------------------------------------------------------
-- toℕ
------------------------------------------------------------------------
toℕ-injective : toℕ i ≡ toℕ j → i ≡ j
toℕ-injective {zero} {} {} _
toℕ-injective {suc n} {zero} {zero} eq = refl
toℕ-injective {suc n} {suc i} {suc j} eq =
cong suc (toℕ-injective (cong ℕ.pred eq))
toℕ-strengthen : ∀ (i : Fin n) → toℕ (strengthen i) ≡ toℕ i
toℕ-strengthen zero = refl
toℕ-strengthen (suc i) = cong suc (toℕ-strengthen i)
------------------------------------------------------------------------
-- toℕ-↑ˡ: "i" ↑ˡ n = "i" in Fin (m + n)
------------------------------------------------------------------------
toℕ-↑ˡ : ∀ (i : Fin m) n → toℕ (i ↑ˡ n) ≡ toℕ i
toℕ-↑ˡ zero n = refl
toℕ-↑ˡ (suc i) n = cong suc (toℕ-↑ˡ i n)
↑ˡ-injective : ∀ n (i j : Fin m) → i ↑ˡ n ≡ j ↑ˡ n → i ≡ j
↑ˡ-injective n zero zero refl = refl
↑ˡ-injective n (suc i) (suc j) eq =
cong suc (↑ˡ-injective n i j (suc-injective eq))
------------------------------------------------------------------------
-- toℕ-↑ʳ: n ↑ʳ "i" = "n + i" in Fin (n + m)
------------------------------------------------------------------------
toℕ-↑ʳ : ∀ n (i : Fin m) → toℕ (n ↑ʳ i) ≡ n ℕ.+ toℕ i
toℕ-↑ʳ zero i = refl
toℕ-↑ʳ (suc n) i = cong suc (toℕ-↑ʳ n i)
↑ʳ-injective : ∀ n (i j : Fin m) → n ↑ʳ i ≡ n ↑ʳ j → i ≡ j
↑ʳ-injective zero i i refl = refl
↑ʳ-injective (suc n) i j eq = ↑ʳ-injective n i j (suc-injective eq)
------------------------------------------------------------------------
-- toℕ and the ordering relations
------------------------------------------------------------------------
toℕ<n : ∀ (i : Fin n) → toℕ i ℕ.< n
toℕ<n {n = suc _} zero = z<s
toℕ<n {n = suc _} (suc i) = s<s (toℕ<n i)
toℕ≤pred[n] : ∀ (i : Fin n) → toℕ i ℕ.≤ ℕ.pred n
toℕ≤pred[n] zero = z≤n
toℕ≤pred[n] (suc {n = suc n} i) = s≤s (toℕ≤pred[n] i)
toℕ≤n : ∀ (i : Fin n) → toℕ i ℕ.≤ n
toℕ≤n {suc n} i = ℕ.m≤n⇒m≤1+n (toℕ≤pred[n] i)
-- A simpler implementation of toℕ≤pred[n],
-- however, with a different reduction behavior.
-- If no one needs the reduction behavior of toℕ≤pred[n],
-- it can be removed in favor of toℕ≤pred[n]′.
toℕ≤pred[n]′ : ∀ (i : Fin n) → toℕ i ℕ.≤ ℕ.pred n
toℕ≤pred[n]′ i = ℕ.<⇒≤pred (toℕ<n i)
toℕ-mono-< : i < j → toℕ i ℕ.< toℕ j
toℕ-mono-< i<j = i<j
toℕ-mono-≤ : i ≤ j → toℕ i ℕ.≤ toℕ j
toℕ-mono-≤ i≤j = i≤j
toℕ-cancel-≤ : toℕ i ℕ.≤ toℕ j → i ≤ j
toℕ-cancel-≤ i≤j = i≤j
toℕ-cancel-< : toℕ i ℕ.< toℕ j → i < j
toℕ-cancel-< i<j = i<j
------------------------------------------------------------------------
-- fromℕ
------------------------------------------------------------------------
toℕ-fromℕ : ∀ n → toℕ (fromℕ n) ≡ n
toℕ-fromℕ zero = refl
toℕ-fromℕ (suc n) = cong suc (toℕ-fromℕ n)
fromℕ-toℕ : ∀ (i : Fin n) → fromℕ (toℕ i) ≡ strengthen i
fromℕ-toℕ zero = refl
fromℕ-toℕ (suc i) = cong suc (fromℕ-toℕ i)
≤fromℕ : ∀ (i : Fin (suc n)) → i ≤ fromℕ n
≤fromℕ {n = n} i rewrite toℕ-fromℕ n = ℕ.s≤s⁻¹ (toℕ<n i)
------------------------------------------------------------------------
-- fromℕ<
------------------------------------------------------------------------
fromℕ<-toℕ : ∀ (i : Fin n) .(i<n : toℕ i ℕ.< n) → fromℕ< i<n ≡ i
fromℕ<-toℕ zero _ = refl
fromℕ<-toℕ (suc i) i<n = cong suc (fromℕ<-toℕ i (ℕ.s<s⁻¹ i<n))
toℕ-fromℕ< : ∀ .(m<n : m ℕ.< n) → toℕ (fromℕ< m<n) ≡ m
toℕ-fromℕ< {m = zero} {n = suc _} _ = refl
toℕ-fromℕ< {m = suc m} {n = suc _} m<n = cong suc (toℕ-fromℕ< (ℕ.s<s⁻¹ m<n))
-- fromℕ is a special case of fromℕ<.
fromℕ-def : ∀ n → fromℕ n ≡ fromℕ< ℕ.≤-refl
fromℕ-def zero = refl
fromℕ-def (suc n) = cong suc (fromℕ-def n)
fromℕ<-cong : ∀ m n {o} → m ≡ n → .(m<o : m ℕ.< o) .(n<o : n ℕ.< o) →
fromℕ< m<o ≡ fromℕ< n<o
fromℕ<-cong 0 0 _ _ _ = refl
fromℕ<-cong (suc _) (suc _) {o = suc _} r m<n n<o
= cong suc (fromℕ<-cong _ _ (ℕ.suc-injective r) (ℕ.s<s⁻¹ m<n) (ℕ.s<s⁻¹ n<o))
fromℕ<-injective : ∀ m n {o} → .(m<o : m ℕ.< o) .(n<o : n ℕ.< o) →
fromℕ< m<o ≡ fromℕ< n<o → m ≡ n
fromℕ<-injective 0 0 _ _ _ = refl
fromℕ<-injective 0 (suc _) {o = suc _} _ _ ()
fromℕ<-injective (suc _) (suc _) {o = suc _} m<n n<o r
= cong suc (fromℕ<-injective _ _ (ℕ.s<s⁻¹ m<n) (ℕ.s<s⁻¹ n<o) (suc-injective r))
------------------------------------------------------------------------
-- fromℕ<″
------------------------------------------------------------------------
fromℕ<≡fromℕ<″ : ∀ (m<n : m ℕ.< n) (m<″n : m ℕ.<″ n) →
fromℕ< m<n ≡ fromℕ<″ m m<″n
fromℕ<≡fromℕ<″ {m = zero} {n = suc _} _ _ = refl
fromℕ<≡fromℕ<″ {m = suc m} {n = suc _} m<n m<″n
= cong suc (fromℕ<≡fromℕ<″ (ℕ.s<s⁻¹ m<n) (ℕ.s<″s⁻¹ m<″n))
toℕ-fromℕ<″ : ∀ (m<n : m ℕ.<″ n) → toℕ (fromℕ<″ m m<n) ≡ m
toℕ-fromℕ<″ {m} {n} m<n = begin
toℕ (fromℕ<″ m m<n) ≡⟨ cong toℕ (sym (fromℕ<≡fromℕ<″ (ℕ.≤″⇒≤ m<n) m<n)) ⟩
toℕ (fromℕ< _) ≡⟨ toℕ-fromℕ< (ℕ.≤″⇒≤ m<n) ⟩
m ∎
where open ≡-Reasoning
------------------------------------------------------------------------
-- Properties of cast
------------------------------------------------------------------------
toℕ-cast : ∀ .(eq : m ≡ n) (k : Fin m) → toℕ (cast eq k) ≡ toℕ k
toℕ-cast {n = suc n} eq zero = refl
toℕ-cast {n = suc n} eq (suc k) = cong suc (toℕ-cast (cong ℕ.pred eq) k)
cast-is-id : .(eq : m ≡ m) (k : Fin m) → cast eq k ≡ k
cast-is-id eq zero = refl
cast-is-id eq (suc k) = cong suc (cast-is-id (ℕ.suc-injective eq) k)
subst-is-cast : (eq : m ≡ n) (k : Fin m) → subst Fin eq k ≡ cast eq k
subst-is-cast refl k = sym (cast-is-id refl k)
cast-trans : .(eq₁ : m ≡ n) .(eq₂ : n ≡ o) (k : Fin m) →
cast eq₂ (cast eq₁ k) ≡ cast (trans eq₁ eq₂) k
cast-trans {m = suc _} {n = suc _} {o = suc _} eq₁ eq₂ zero = refl
cast-trans {m = suc _} {n = suc _} {o = suc _} eq₁ eq₂ (suc k) =
cong suc (cast-trans (ℕ.suc-injective eq₁) (ℕ.suc-injective eq₂) k)
------------------------------------------------------------------------
-- Properties of _≤_
------------------------------------------------------------------------
-- Relational properties
≤-reflexive : _≡_ ⇒ (_≤_ {n})
≤-reflexive refl = ℕ.≤-refl
≤-refl : Reflexive (_≤_ {n})
≤-refl = ≤-reflexive refl
≤-trans : Transitive (_≤_ {n})
≤-trans = ℕ.≤-trans
≤-antisym : Antisymmetric _≡_ (_≤_ {n})
≤-antisym x≤y y≤x = toℕ-injective (ℕ.≤-antisym x≤y y≤x)
≤-total : Total (_≤_ {n})
≤-total x y = ℕ.≤-total (toℕ x) (toℕ y)
≤-irrelevant : Irrelevant (_≤_ {m} {n})
≤-irrelevant = ℕ.≤-irrelevant
infix 4 _≤?_ _<?_
_≤?_ : B.Decidable (_≤_ {m} {n})
a ≤? b = toℕ a ℕ.≤? toℕ b
_<?_ : B.Decidable (_<_ {m} {n})
m <? n = suc (toℕ m) ℕ.≤? toℕ n
------------------------------------------------------------------------
-- Structures
≤-isPreorder : IsPreorder {A = Fin n} _≡_ _≤_
≤-isPreorder = record
{ isEquivalence = ≡.isEquivalence
; reflexive = ≤-reflexive
; trans = ≤-trans
}
≤-isPartialOrder : IsPartialOrder {A = Fin n} _≡_ _≤_
≤-isPartialOrder = record
{ isPreorder = ≤-isPreorder
; antisym = ≤-antisym
}
≤-isTotalOrder : IsTotalOrder {A = Fin n} _≡_ _≤_
≤-isTotalOrder = record
{ isPartialOrder = ≤-isPartialOrder
; total = ≤-total
}
≤-isDecTotalOrder : IsDecTotalOrder {A = Fin n} _≡_ _≤_
≤-isDecTotalOrder = record
{ isTotalOrder = ≤-isTotalOrder
; _≟_ = _≟_
; _≤?_ = _≤?_
}
------------------------------------------------------------------------
-- Bundles
≤-preorder : ℕ → Preorder _ _ _
≤-preorder n = record
{ isPreorder = ≤-isPreorder {n}
}
≤-poset : ℕ → Poset _ _ _
≤-poset n = record
{ isPartialOrder = ≤-isPartialOrder {n}
}
≤-totalOrder : ℕ → TotalOrder _ _ _
≤-totalOrder n = record
{ isTotalOrder = ≤-isTotalOrder {n}
}
≤-decTotalOrder : ℕ → DecTotalOrder _ _ _
≤-decTotalOrder n = record
{ isDecTotalOrder = ≤-isDecTotalOrder {n}
}
------------------------------------------------------------------------
-- Properties of _<_
------------------------------------------------------------------------
-- Relational properties
<-irrefl : Irreflexive _≡_ (_<_ {n})
<-irrefl refl = ℕ.<-irrefl refl
<-asym : Asymmetric (_<_ {n})
<-asym = ℕ.<-asym
<-trans : Transitive (_<_ {n})
<-trans = ℕ.<-trans
<-cmp : Trichotomous _≡_ (_<_ {n})
<-cmp zero zero = tri≈ (λ()) refl (λ())
<-cmp zero (suc j) = tri< z<s (λ()) (λ())
<-cmp (suc i) zero = tri> (λ()) (λ()) z<s
<-cmp (suc i) (suc j) with <-cmp i j
... | tri< i<j i≢j j≮i = tri< (s<s i<j) (i≢j ∘ suc-injective) (j≮i ∘ s<s⁻¹)
... | tri> i≮j i≢j j<i = tri> (i≮j ∘ s<s⁻¹) (i≢j ∘ suc-injective) (s<s j<i)
... | tri≈ i≮j i≡j j≮i = tri≈ (i≮j ∘ s<s⁻¹) (cong suc i≡j) (j≮i ∘ s<s⁻¹)
<-respˡ-≡ : (_<_ {m} {n}) Respectsˡ _≡_
<-respˡ-≡ refl x≤y = x≤y
<-respʳ-≡ : (_<_ {m} {n}) Respectsʳ _≡_
<-respʳ-≡ refl x≤y = x≤y
<-resp₂-≡ : (_<_ {n}) Respects₂ _≡_
<-resp₂-≡ = <-respˡ-≡ , <-respʳ-≡
<-irrelevant : Irrelevant (_<_ {m} {n})
<-irrelevant = ℕ.<-irrelevant
------------------------------------------------------------------------
-- Structures
<-isStrictPartialOrder : IsStrictPartialOrder {A = Fin n} _≡_ _<_
<-isStrictPartialOrder = record
{ isEquivalence = ≡.isEquivalence
; irrefl = <-irrefl
; trans = <-trans
; <-resp-≈ = <-resp₂-≡
}
<-isStrictTotalOrder : IsStrictTotalOrder {A = Fin n} _≡_ _<_
<-isStrictTotalOrder = record
{ isStrictPartialOrder = <-isStrictPartialOrder
; compare = <-cmp
}
------------------------------------------------------------------------
-- Bundles
<-strictPartialOrder : ℕ → StrictPartialOrder _ _ _
<-strictPartialOrder n = record
{ isStrictPartialOrder = <-isStrictPartialOrder {n}
}
<-strictTotalOrder : ℕ → StrictTotalOrder _ _ _
<-strictTotalOrder n = record
{ isStrictTotalOrder = <-isStrictTotalOrder {n}
}
------------------------------------------------------------------------
-- Other properties
i<1+i : ∀ (i : Fin n) → i < suc i
i<1+i = ℕ.n<1+n ∘ toℕ
<⇒≢ : i < j → i ≢ j
<⇒≢ i<i refl = ℕ.n≮n _ i<i
≤∧≢⇒< : i ≤ j → i ≢ j → i < j
≤∧≢⇒< {i = zero} {zero} _ 0≢0 = contradiction refl 0≢0
≤∧≢⇒< {i = zero} {suc j} _ _ = z<s
≤∧≢⇒< {i = suc i} {suc j} 1+i≤1+j 1+i≢1+j =
s<s (≤∧≢⇒< (ℕ.s≤s⁻¹ 1+i≤1+j) (1+i≢1+j ∘ (cong suc)))
------------------------------------------------------------------------
-- inject
------------------------------------------------------------------------
toℕ-inject : ∀ {i : Fin n} (j : Fin′ i) → toℕ (inject j) ≡ toℕ j
toℕ-inject {i = suc i} zero = refl
toℕ-inject {i = suc i} (suc j) = cong suc (toℕ-inject j)
------------------------------------------------------------------------
-- inject₁
------------------------------------------------------------------------
fromℕ≢inject₁ : fromℕ n ≢ inject₁ i
fromℕ≢inject₁ {i = suc i} eq = fromℕ≢inject₁ {i = i} (suc-injective eq)
inject₁-injective : inject₁ i ≡ inject₁ j → i ≡ j
inject₁-injective {i = zero} {zero} i≡j = refl
inject₁-injective {i = suc i} {suc j} i≡j =
cong suc (inject₁-injective (suc-injective i≡j))
toℕ-inject₁ : ∀ (i : Fin n) → toℕ (inject₁ i) ≡ toℕ i
toℕ-inject₁ zero = refl
toℕ-inject₁ (suc i) = cong suc (toℕ-inject₁ i)
toℕ-inject₁-≢ : ∀ (i : Fin n) → n ≢ toℕ (inject₁ i)
toℕ-inject₁-≢ (suc i) = toℕ-inject₁-≢ i ∘ ℕ.suc-injective
inject₁ℕ< : ∀ (i : Fin n) → toℕ (inject₁ i) ℕ.< n
inject₁ℕ< i rewrite toℕ-inject₁ i = toℕ<n i
inject₁ℕ≤ : ∀ (i : Fin n) → toℕ (inject₁ i) ℕ.≤ n
inject₁ℕ≤ = ℕ.<⇒≤ ∘ inject₁ℕ<
≤̄⇒inject₁< : i ≤ j → inject₁ i < suc j
≤̄⇒inject₁< {i = i} i≤j rewrite sym (toℕ-inject₁ i) = s<s i≤j
ℕ<⇒inject₁< : ∀ {i : Fin (ℕ.suc n)} {j : Fin n} → j < i → inject₁ j < i
ℕ<⇒inject₁< {i = suc i} j≤i = ≤̄⇒inject₁< (ℕ.s≤s⁻¹ j≤i)
i≤inject₁[j]⇒i≤1+j : i ≤ inject₁ j → i ≤ suc j
i≤inject₁[j]⇒i≤1+j {i = zero} _ = z≤n
i≤inject₁[j]⇒i≤1+j {i = suc i} {j = suc j} i≤j = s≤s (ℕ.m≤n⇒m≤1+n (subst (toℕ i ℕ.≤_) (toℕ-inject₁ j) (ℕ.s≤s⁻¹ i≤j)))
------------------------------------------------------------------------
-- lower₁
------------------------------------------------------------------------
toℕ-lower₁ : ∀ i (p : n ≢ toℕ i) → toℕ (lower₁ i p) ≡ toℕ i
toℕ-lower₁ {ℕ.zero} zero p = contradiction refl p
toℕ-lower₁ {ℕ.suc m} zero p = refl
toℕ-lower₁ {ℕ.suc m} (suc i) p = cong ℕ.suc (toℕ-lower₁ i (p ∘ cong ℕ.suc))
lower₁-injective : ∀ {n≢i : n ≢ toℕ i} {n≢j : n ≢ toℕ j} →
lower₁ i n≢i ≡ lower₁ j n≢j → i ≡ j
lower₁-injective {zero} {zero} {_} {n≢i} {_} _ = contradiction refl n≢i
lower₁-injective {zero} {_} {zero} {_} {n≢j} _ = contradiction refl n≢j
lower₁-injective {suc n} {zero} {zero} {_} {_} refl = refl
lower₁-injective {suc n} {suc i} {suc j} {n≢i} {n≢j} eq =
cong suc (lower₁-injective (suc-injective eq))
------------------------------------------------------------------------
-- inject₁ and lower₁
inject₁-lower₁ : ∀ (i : Fin (suc n)) (n≢i : n ≢ toℕ i) →
inject₁ (lower₁ i n≢i) ≡ i
inject₁-lower₁ {zero} zero 0≢0 = contradiction refl 0≢0
inject₁-lower₁ {suc n} zero _ = refl
inject₁-lower₁ {suc n} (suc i) n+1≢i+1 =
cong suc (inject₁-lower₁ i (n+1≢i+1 ∘ cong suc))
lower₁-inject₁′ : ∀ (i : Fin n) (n≢i : n ≢ toℕ (inject₁ i)) →
lower₁ (inject₁ i) n≢i ≡ i
lower₁-inject₁′ zero _ = refl
lower₁-inject₁′ (suc i) n+1≢i+1 =
cong suc (lower₁-inject₁′ i (n+1≢i+1 ∘ cong suc))
lower₁-inject₁ : ∀ (i : Fin n) →
lower₁ (inject₁ i) (toℕ-inject₁-≢ i) ≡ i
lower₁-inject₁ i = lower₁-inject₁′ i (toℕ-inject₁-≢ i)
lower₁-irrelevant : ∀ (i : Fin (suc n)) (n≢i₁ n≢i₂ : n ≢ toℕ i) →
lower₁ i n≢i₁ ≡ lower₁ i n≢i₂
lower₁-irrelevant {zero} zero 0≢0 _ = contradiction refl 0≢0
lower₁-irrelevant {suc n} zero _ _ = refl
lower₁-irrelevant {suc n} (suc i) _ _ =
cong suc (lower₁-irrelevant i _ _)
inject₁≡⇒lower₁≡ : ∀ {i : Fin n} {j : Fin (ℕ.suc n)} →
(n≢j : n ≢ toℕ j) → inject₁ i ≡ j → lower₁ j n≢j ≡ i
inject₁≡⇒lower₁≡ n≢j i≡j = inject₁-injective (trans (inject₁-lower₁ _ n≢j) (sym i≡j))
------------------------------------------------------------------------
-- inject≤
------------------------------------------------------------------------
toℕ-inject≤ : ∀ i .(m≤n : m ℕ.≤ n) → toℕ (inject≤ i m≤n) ≡ toℕ i
toℕ-inject≤ {_} {suc n} zero _ = refl
toℕ-inject≤ {_} {suc n} (suc i) _ = cong suc (toℕ-inject≤ i _)
inject≤-refl : ∀ i .(n≤n : n ℕ.≤ n) → inject≤ i n≤n ≡ i
inject≤-refl {suc n} zero _ = refl
inject≤-refl {suc n} (suc i) _ = cong suc (inject≤-refl i _)
inject≤-idempotent : ∀ (i : Fin m)
.(m≤n : m ℕ.≤ n) .(n≤o : n ℕ.≤ o) .(m≤o : m ℕ.≤ o) →
inject≤ (inject≤ i m≤n) n≤o ≡ inject≤ i m≤o
inject≤-idempotent {_} {suc n} {suc o} zero _ _ _ = refl
inject≤-idempotent {_} {suc n} {suc o} (suc i) _ _ _ =
cong suc (inject≤-idempotent i _ _ _)
inject≤-trans : ∀ (i : Fin m) .(m≤n : m ℕ.≤ n) .(n≤o : n ℕ.≤ o) →
inject≤ (inject≤ i m≤n) n≤o ≡ inject≤ i (ℕ.≤-trans m≤n n≤o)
inject≤-trans i _ _ = inject≤-idempotent i _ _ _
inject≤-injective : ∀ .(m≤n m≤n′ : m ℕ.≤ n) i j →
inject≤ i m≤n ≡ inject≤ j m≤n′ → i ≡ j
inject≤-injective {n = suc _} _ _ zero zero eq = refl
inject≤-injective {n = suc _} _ _ (suc i) (suc j) eq =
cong suc (inject≤-injective _ _ i j (suc-injective eq))
inject≤-irrelevant : ∀ .(m≤n m≤n′ : m ℕ.≤ n) i →
inject≤ i m≤n ≡ inject≤ i m≤n′
inject≤-irrelevant _ _ i = refl
------------------------------------------------------------------------
-- pred
------------------------------------------------------------------------
pred< : ∀ (i : Fin (suc n)) → i ≢ zero → pred i < i
pred< zero i≢0 = contradiction refl i≢0
pred< (suc i) _ = ≤̄⇒inject₁< ℕ.≤-refl
------------------------------------------------------------------------
-- splitAt
------------------------------------------------------------------------
-- Fin (m + n) ↔ Fin m ⊎ Fin n
splitAt-↑ˡ : ∀ m i n → splitAt m (i ↑ˡ n) ≡ inj₁ i
splitAt-↑ˡ (suc m) zero n = refl
splitAt-↑ˡ (suc m) (suc i) n rewrite splitAt-↑ˡ m i n = refl
splitAt⁻¹-↑ˡ : ∀ {m} {n} {i} {j} → splitAt m {n} i ≡ inj₁ j → j ↑ˡ n ≡ i
splitAt⁻¹-↑ˡ {suc m} {n} {0F} {.0F} refl = refl
splitAt⁻¹-↑ˡ {suc m} {n} {suc i} {j} eq
with inj₁ k ← splitAt m i in splitAt[m][i]≡inj₁[j]
with refl ← eq
= cong suc (splitAt⁻¹-↑ˡ {i = i} {j = k} splitAt[m][i]≡inj₁[j])
splitAt-↑ʳ : ∀ m n i → splitAt m (m ↑ʳ i) ≡ inj₂ {B = Fin n} i
splitAt-↑ʳ zero n i = refl
splitAt-↑ʳ (suc m) n i rewrite splitAt-↑ʳ m n i = refl
splitAt⁻¹-↑ʳ : ∀ {m} {n} {i} {j} → splitAt m {n} i ≡ inj₂ j → m ↑ʳ j ≡ i
splitAt⁻¹-↑ʳ {zero} {n} {i} {j} refl = refl
splitAt⁻¹-↑ʳ {suc m} {n} {suc i} {j} eq
with inj₂ k ← splitAt m i in splitAt[m][i]≡inj₂[k]
with refl ← eq
= cong suc (splitAt⁻¹-↑ʳ {i = i} {j = k} splitAt[m][i]≡inj₂[k])
splitAt-join : ∀ m n i → splitAt m (join m n i) ≡ i
splitAt-join m n (inj₁ x) = splitAt-↑ˡ m x n
splitAt-join m n (inj₂ y) = splitAt-↑ʳ m n y
join-splitAt : ∀ m n i → join m n (splitAt m i) ≡ i
join-splitAt zero n i = refl
join-splitAt (suc m) n zero = refl
join-splitAt (suc m) n (suc i) = begin
[ _↑ˡ n , (suc m) ↑ʳ_ ]′ (splitAt (suc m) (suc i)) ≡⟨ [,]-map (splitAt m i) ⟩
[ suc ∘ (_↑ˡ n) , suc ∘ (m ↑ʳ_) ]′ (splitAt m i) ≡⟨ [,]-∘ suc (splitAt m i) ⟨
suc ([ _↑ˡ n , m ↑ʳ_ ]′ (splitAt m i)) ≡⟨ cong suc (join-splitAt m n i) ⟩
suc i ∎
where open ≡-Reasoning
-- splitAt "m" "i" ≡ inj₁ "i" if i < m
splitAt-< : ∀ m {n} (i : Fin (m ℕ.+ n)) .(i<m : toℕ i ℕ.< m) →
splitAt m i ≡ inj₁ (fromℕ< i<m)
splitAt-< (suc m) zero _ = refl
splitAt-< (suc m) (suc i) i<m = cong (Sum.map suc id) (splitAt-< m i (ℕ.s<s⁻¹ i<m))
-- splitAt "m" "i" ≡ inj₂ "i - m" if i ≥ m
splitAt-≥ : ∀ m {n} (i : Fin (m ℕ.+ n)) .(i≥m : toℕ i ℕ.≥ m) →
splitAt m i ≡ inj₂ (reduce≥ i i≥m)
splitAt-≥ zero i _ = refl
splitAt-≥ (suc m) (suc i) i≥m = cong (Sum.map suc id) (splitAt-≥ m i (ℕ.s≤s⁻¹ i≥m))
------------------------------------------------------------------------
-- Bundles
+↔⊎ : Fin (m ℕ.+ n) ↔ (Fin m ⊎ Fin n)
+↔⊎ {m} {n} = mk↔ₛ′ (splitAt m {n}) (join m n) (splitAt-join m n) (join-splitAt m n)
------------------------------------------------------------------------
-- remQuot
------------------------------------------------------------------------
-- Fin (m * n) ↔ Fin m × Fin n
remQuot-combine : ∀ {n k} (i : Fin n) j → remQuot k (combine i j) ≡ (i , j)
remQuot-combine {suc n} {k} zero j rewrite splitAt-↑ˡ k j (n ℕ.* k) = refl
remQuot-combine {suc n} {k} (suc i) j rewrite splitAt-↑ʳ k (n ℕ.* k) (combine i j) =
cong (Product.map₁ suc) (remQuot-combine i j)
combine-remQuot : ∀ {n} k (i : Fin (n ℕ.* k)) → uncurry combine (remQuot {n} k i) ≡ i
combine-remQuot {suc n} k i with splitAt k i in eq
... | inj₁ j = begin
join k (n ℕ.* k) (inj₁ j) ≡⟨ cong (join k (n ℕ.* k)) eq ⟨
join k (n ℕ.* k) (splitAt k i) ≡⟨ join-splitAt k (n ℕ.* k) i ⟩
i ∎
where open ≡-Reasoning
... | inj₂ j = begin
k ↑ʳ (uncurry combine (remQuot {n} k j)) ≡⟨ cong (k ↑ʳ_) (combine-remQuot {n} k j) ⟩
join k (n ℕ.* k) (inj₂ j) ≡⟨ cong (join k (n ℕ.* k)) eq ⟨
join k (n ℕ.* k) (splitAt k i) ≡⟨ join-splitAt k (n ℕ.* k) i ⟩
i ∎
where open ≡-Reasoning
toℕ-combine : ∀ (i : Fin m) (j : Fin n) → toℕ (combine i j) ≡ n ℕ.* toℕ i ℕ.+ toℕ j
toℕ-combine {suc m} {n} i@0F j = begin
toℕ (combine i j) ≡⟨⟩
toℕ (j ↑ˡ (m ℕ.* n)) ≡⟨ toℕ-↑ˡ j (m ℕ.* n) ⟩
toℕ j ≡⟨⟩
0 ℕ.+ toℕ j ≡⟨ cong (ℕ._+ toℕ j) (ℕ.*-zeroʳ n) ⟨
n ℕ.* toℕ i ℕ.+ toℕ j ∎
where open ≡-Reasoning
toℕ-combine {suc m} {n} (suc i) j = begin
toℕ (combine (suc i) j) ≡⟨⟩
toℕ (n ↑ʳ combine i j) ≡⟨ toℕ-↑ʳ n (combine i j) ⟩
n ℕ.+ toℕ (combine i j) ≡⟨ cong (n ℕ.+_) (toℕ-combine i j) ⟩
n ℕ.+ (n ℕ.* toℕ i ℕ.+ toℕ j) ≡⟨ ℕ.+-assoc n _ (toℕ j) ⟨
n ℕ.+ n ℕ.* toℕ i ℕ.+ toℕ j ≡⟨ cong (λ z → z ℕ.+ n ℕ.* toℕ i ℕ.+ toℕ j) (ℕ.*-identityʳ n) ⟨
n ℕ.* 1 ℕ.+ n ℕ.* toℕ i ℕ.+ toℕ j ≡⟨ cong (ℕ._+ toℕ j) (ℕ.*-distribˡ-+ n 1 (toℕ i) ) ⟨
n ℕ.* toℕ (suc i) ℕ.+ toℕ j ∎
where open ≡-Reasoning
combine-monoˡ-< : ∀ {i j : Fin m} (k l : Fin n) →
i < j → combine i k < combine j l
combine-monoˡ-< {m} {n} {i} {j} k l i<j = begin-strict
toℕ (combine i k) ≡⟨ toℕ-combine i k ⟩
n ℕ.* toℕ i ℕ.+ toℕ k <⟨ ℕ.+-monoʳ-< (n ℕ.* toℕ i) (toℕ<n k) ⟩
n ℕ.* toℕ i ℕ.+ n ≡⟨ ℕ.+-comm _ n ⟩
n ℕ.+ n ℕ.* toℕ i ≡⟨ cong (n ℕ.+_) (ℕ.*-comm n _) ⟩
n ℕ.+ toℕ i ℕ.* n ≡⟨ ℕ.*-comm (suc (toℕ i)) n ⟩
n ℕ.* suc (toℕ i) ≤⟨ ℕ.*-monoʳ-≤ n (toℕ-mono-< i<j) ⟩
n ℕ.* toℕ j ≤⟨ ℕ.m≤m+n (n ℕ.* toℕ j) (toℕ l) ⟩
n ℕ.* toℕ j ℕ.+ toℕ l ≡⟨ toℕ-combine j l ⟨
toℕ (combine j l) ∎
where open ℕ.≤-Reasoning
combine-injectiveˡ : ∀ (i : Fin m) (j : Fin n) (k : Fin m) (l : Fin n) →
combine i j ≡ combine k l → i ≡ k
combine-injectiveˡ i j k l cᵢⱼ≡cₖₗ with <-cmp i k
... | tri< i<k _ _ = contradiction cᵢⱼ≡cₖₗ (<⇒≢ (combine-monoˡ-< j l i<k))
... | tri≈ _ i≡k _ = i≡k
... | tri> _ _ i>k = contradiction (sym cᵢⱼ≡cₖₗ) (<⇒≢ (combine-monoˡ-< l j i>k))
combine-injectiveʳ : ∀ (i : Fin m) (j : Fin n) (k : Fin m) (l : Fin n) →
combine i j ≡ combine k l → j ≡ l
combine-injectiveʳ {m} {n} i j k l cᵢⱼ≡cₖₗ
with refl ← combine-injectiveˡ i j k l cᵢⱼ≡cₖₗ
= toℕ-injective (ℕ.+-cancelˡ-≡ (n ℕ.* toℕ i) _ _ (begin
n ℕ.* toℕ i ℕ.+ toℕ j ≡⟨ toℕ-combine i j ⟨
toℕ (combine i j) ≡⟨ cong toℕ cᵢⱼ≡cₖₗ ⟩
toℕ (combine i l) ≡⟨ toℕ-combine i l ⟩
n ℕ.* toℕ i ℕ.+ toℕ l ∎))
where open ≡-Reasoning
combine-injective : ∀ (i : Fin m) (j : Fin n) (k : Fin m) (l : Fin n) →
combine i j ≡ combine k l → i ≡ k × j ≡ l
combine-injective i j k l cᵢⱼ≡cₖₗ =
combine-injectiveˡ i j k l cᵢⱼ≡cₖₗ ,
combine-injectiveʳ i j k l cᵢⱼ≡cₖₗ
combine-surjective : ∀ (i : Fin (m ℕ.* n)) → ∃₂ λ j k → combine j k ≡ i
combine-surjective {m} {n} i with j , k ← remQuot {m} n i in eq
= j , k , (begin
combine j k ≡⟨ uncurry (cong₂ combine) (,-injective eq) ⟨
uncurry combine (remQuot {m} n i) ≡⟨ combine-remQuot {m} n i ⟩
i ∎)
where open ≡-Reasoning
------------------------------------------------------------------------
-- Bundles
*↔× : Fin (m ℕ.* n) ↔ (Fin m × Fin n)
*↔× {m} {n} = mk↔ₛ′ (remQuot {m} n) (uncurry combine)
(uncurry remQuot-combine)
(combine-remQuot {m} n)
------------------------------------------------------------------------
-- fin→fun
------------------------------------------------------------------------
funToFin-finToFin : funToFin {m} {n} ∘ finToFun ≗ id
funToFin-finToFin {zero} {n} zero = refl
funToFin-finToFin {suc m} {n} k =
begin
combine (finToFun {n} {suc m} k zero) (funToFin (finToFun {n} {suc m} k ∘ suc))
≡⟨⟩
combine (quotient {n} (n ^ m) k)
(funToFin (finToFun {n} {m} (remainder {n} (n ^ m) k)))
≡⟨ cong (combine (quotient {n} (n ^ m) k))
(funToFin-finToFin {m} (remainder {n} (n ^ m) k)) ⟩
combine (quotient {n} (n ^ m) k) (remainder {n} (n ^ m) k)
≡⟨⟩
uncurry combine (remQuot {n} (n ^ m) k)
≡⟨ combine-remQuot {n = n} (n ^ m) k ⟩
k
∎ where open ≡-Reasoning
finToFun-funToFin : (f : Fin m → Fin n) → finToFun (funToFin f) ≗ f
finToFun-funToFin {suc m} {n} f zero =
begin
quotient (n ^ m) (combine (f zero) (funToFin (f ∘ suc)))
≡⟨ cong proj₁ (remQuot-combine _ _) ⟩
proj₁ (f zero , funToFin (f ∘ suc))
≡⟨⟩
f zero
∎ where open ≡-Reasoning
finToFun-funToFin {suc m} {n} f (suc i) =
begin
finToFun (remainder {n} (n ^ m) (combine (f zero) (funToFin (f ∘ suc)))) i
≡⟨ cong (λ rq → finToFun (proj₂ rq) i) (remQuot-combine {n} _ _) ⟩
finToFun (proj₂ (f zero , funToFin (f ∘ suc))) i
≡⟨⟩
finToFun (funToFin (f ∘ suc)) i
≡⟨ finToFun-funToFin (f ∘ suc) i ⟩
(f ∘ suc) i
≡⟨⟩
f (suc i)
∎ where open ≡-Reasoning
------------------------------------------------------------------------
-- Bundles
^↔→ : Extensionality _ _ → Fin (m ^ n) ↔ (Fin n → Fin m)
^↔→ {m} {n} ext = mk↔ₛ′ finToFun funToFin
(ext ∘ finToFun-funToFin)
(funToFin-finToFin {n} {m})
------------------------------------------------------------------------
-- lift
------------------------------------------------------------------------
lift-injective : ∀ (f : Fin m → Fin n) → Injective _≡_ _≡_ f →
∀ k → Injective _≡_ _≡_ (lift k f)
lift-injective f inj zero {_} {_} eq = inj eq
lift-injective f inj (suc k) {zero} {zero} eq = refl
lift-injective f inj (suc k) {suc _} {suc _} eq =
cong suc (lift-injective f inj k (suc-injective eq))
------------------------------------------------------------------------
-- pred
------------------------------------------------------------------------
<⇒≤pred : i < j → i ≤ pred j
<⇒≤pred {i = zero} {j = suc j} z<s = z≤n
<⇒≤pred {i = suc i} {j = suc j} (s<s i<j) rewrite toℕ-inject₁ j = i<j
------------------------------------------------------------------------
-- _ℕ-_
------------------------------------------------------------------------
toℕ‿ℕ- : ∀ n i → toℕ (n ℕ- i) ≡ n ∸ toℕ i
toℕ‿ℕ- n zero = toℕ-fromℕ n
toℕ‿ℕ- (suc n) (suc i) = toℕ‿ℕ- n i
------------------------------------------------------------------------
-- _ℕ-ℕ_
------------------------------------------------------------------------
ℕ-ℕ≡toℕ‿ℕ- : ∀ n i → n ℕ-ℕ i ≡ toℕ (n ℕ- i)
ℕ-ℕ≡toℕ‿ℕ- n zero = sym (toℕ-fromℕ n)
ℕ-ℕ≡toℕ‿ℕ- (suc n) (suc i) = ℕ-ℕ≡toℕ‿ℕ- n i
nℕ-ℕi≤n : ∀ n i → n ℕ-ℕ i ℕ.≤ n
nℕ-ℕi≤n n zero = ℕ.≤-refl
nℕ-ℕi≤n (suc n) (suc i) = begin
n ℕ-ℕ i ≤⟨ nℕ-ℕi≤n n i ⟩
n ≤⟨ ℕ.n≤1+n n ⟩
suc n ∎
where open ℕ.≤-Reasoning
------------------------------------------------------------------------
-- punchIn
------------------------------------------------------------------------
punchIn-injective : ∀ i (j k : Fin n) →
punchIn i j ≡ punchIn i k → j ≡ k
punchIn-injective zero _ _ refl = refl
punchIn-injective (suc i) zero zero _ = refl
punchIn-injective (suc i) (suc j) (suc k) ↑j+1≡↑k+1 =
cong suc (punchIn-injective i j k (suc-injective ↑j+1≡↑k+1))
punchInᵢ≢i : ∀ i (j : Fin n) → punchIn i j ≢ i
punchInᵢ≢i (suc i) (suc j) = punchInᵢ≢i i j ∘ suc-injective
------------------------------------------------------------------------
-- punchOut
------------------------------------------------------------------------
-- A version of 'cong' for 'punchOut' in which the inequality argument
-- can be changed out arbitrarily (reflecting the proof-irrelevance of
-- that argument).
punchOut-cong : ∀ (i : Fin (suc n)) {j k} {i≢j : i ≢ j} {i≢k : i ≢ k} →
j ≡ k → punchOut i≢j ≡ punchOut i≢k
punchOut-cong {_} zero {zero} {i≢j = 0≢0} = contradiction refl 0≢0
punchOut-cong {_} zero {suc j} {zero} {i≢k = 0≢0} = contradiction refl 0≢0
punchOut-cong {_} zero {suc j} {suc k} = suc-injective
punchOut-cong {suc n} (suc i) {zero} {zero} _ = refl
punchOut-cong {suc n} (suc i) {suc j} {suc k} = cong suc ∘ punchOut-cong i ∘ suc-injective
-- An alternative to 'punchOut-cong' in the which the new inequality
-- argument is specific. Useful for enabling the omission of that
-- argument during equational reasoning.
punchOut-cong′ : ∀ (i : Fin (suc n)) {j k} {p : i ≢ j} (q : j ≡ k) →
punchOut p ≡ punchOut (p ∘ sym ∘ trans q ∘ sym)
punchOut-cong′ i q = punchOut-cong i q
punchOut-injective : ∀ {i j k : Fin (suc n)}
(i≢j : i ≢ j) (i≢k : i ≢ k) →
punchOut i≢j ≡ punchOut i≢k → j ≡ k
punchOut-injective {_} {zero} {zero} {_} 0≢0 _ _ = contradiction refl 0≢0
punchOut-injective {_} {zero} {_} {zero} _ 0≢0 _ = contradiction refl 0≢0
punchOut-injective {_} {zero} {suc j} {suc k} _ _ pⱼ≡pₖ = cong suc pⱼ≡pₖ
punchOut-injective {suc n} {suc i} {zero} {zero} _ _ _ = refl
punchOut-injective {suc n} {suc i} {suc j} {suc k} i≢j i≢k pⱼ≡pₖ =
cong suc (punchOut-injective (i≢j ∘ cong suc) (i≢k ∘ cong suc) (suc-injective pⱼ≡pₖ))
punchIn-punchOut : ∀ {i j : Fin (suc n)} (i≢j : i ≢ j) →
punchIn i (punchOut i≢j) ≡ j
punchIn-punchOut {_} {zero} {zero} 0≢0 = contradiction refl 0≢0
punchIn-punchOut {_} {zero} {suc j} _ = refl
punchIn-punchOut {suc m} {suc i} {zero} i≢j = refl
punchIn-punchOut {suc m} {suc i} {suc j} i≢j =
cong suc (punchIn-punchOut (i≢j ∘ cong suc))
punchOut-punchIn : ∀ i {j : Fin n} → punchOut {i = i} {j = punchIn i j} (punchInᵢ≢i i j ∘ sym) ≡ j
punchOut-punchIn zero {j} = refl
punchOut-punchIn (suc i) {zero} = refl
punchOut-punchIn (suc i) {suc j} = cong suc (begin
punchOut (punchInᵢ≢i i j ∘ suc-injective ∘ sym ∘ cong suc) ≡⟨ punchOut-cong i refl ⟩
punchOut (punchInᵢ≢i i j ∘ sym) ≡⟨ punchOut-punchIn i ⟩
j ∎)
where open ≡-Reasoning
------------------------------------------------------------------------
-- pinch
------------------------------------------------------------------------
pinch-surjective : ∀ (i : Fin n) → Surjective _≡_ _≡_ (pinch i)
pinch-surjective _ zero = zero , λ { refl → refl }
pinch-surjective zero (suc j) = suc (suc j) , λ { refl → refl }
pinch-surjective (suc i) (suc j) = map suc (λ {f refl → cong suc (f refl)}) (pinch-surjective i j)
pinch-mono-≤ : ∀ (i : Fin n) → (pinch i) Preserves _≤_ ⟶ _≤_
pinch-mono-≤ 0F {0F} {k} 0≤n = z≤n
pinch-mono-≤ 0F {suc j} {suc k} j≤k = ℕ.s≤s⁻¹ j≤k
pinch-mono-≤ (suc i) {0F} {k} 0≤n = z≤n
pinch-mono-≤ (suc i) {suc j} {suc k} j≤k = s≤s (pinch-mono-≤ i (ℕ.s≤s⁻¹ j≤k))
pinch-injective : ∀ {i : Fin n} {j k : Fin (ℕ.suc n)} →
suc i ≢ j → suc i ≢ k → pinch i j ≡ pinch i k → j ≡ k
pinch-injective {i = i} {zero} {zero} _ _ _ = refl
pinch-injective {i = zero} {zero} {suc k} _ 1+i≢k eq =
contradiction (cong suc eq) 1+i≢k
pinch-injective {i = zero} {suc j} {zero} 1+i≢j _ eq =
contradiction (cong suc (sym eq)) 1+i≢j
pinch-injective {i = zero} {suc j} {suc k} _ _ eq =
cong suc eq
pinch-injective {i = suc i} {suc j} {suc k} 1+i≢j 1+i≢k eq =
cong suc
(pinch-injective (1+i≢j ∘ cong suc) (1+i≢k ∘ cong suc)
(suc-injective eq))
------------------------------------------------------------------------
-- Quantification
------------------------------------------------------------------------
module _ {p} {P : Pred (Fin (suc n)) p} where
∀-cons : P zero → Π[ P ∘ suc ] → Π[ P ]
∀-cons z s zero = z
∀-cons z s (suc i) = s i
∀-cons-⇔ : (P zero × Π[ P ∘ suc ]) ⇔ Π[ P ]
∀-cons-⇔ = mk⇔ (uncurry ∀-cons) < _$ zero , _∘ suc >
∃-here : P zero → ∃⟨ P ⟩
∃-here = zero ,_
∃-there : ∃⟨ P ∘ suc ⟩ → ∃⟨ P ⟩
∃-there = map suc id
∃-toSum : ∃⟨ P ⟩ → P zero ⊎ ∃⟨ P ∘ suc ⟩
∃-toSum ( zero , P₀ ) = inj₁ P₀
∃-toSum (suc f , P₁₊) = inj₂ (f , P₁₊)
⊎⇔∃ : (P zero ⊎ ∃⟨ P ∘ suc ⟩) ⇔ ∃⟨ P ⟩
⊎⇔∃ = mk⇔ [ ∃-here , ∃-there ] ∃-toSum
decFinSubset : ∀ {p q} {P : Pred (Fin n) p} {Q : Pred (Fin n) q} →
Decidable Q → (∀ {i} → Q i → Dec (P i)) → Dec (Q ⊆ P)
decFinSubset {zero} {_} {_} Q? P? = yes λ {}
decFinSubset {suc n} {P = P} {Q} Q? P?
with Q? zero | ∀-cons {P = λ x → Q x → P x}
... | false because [¬Q0] | cons =
map′ (λ f {x} → cons (⊥-elim ∘ invert [¬Q0]) (λ x → f {x}) x)
(λ f {x} → f {suc x})
(decFinSubset (Q? ∘ suc) P?)
... | true because [Q0] | cons =
map′ (uncurry λ P0 rec {x} → cons (λ _ → P0) (λ x → rec {x}) x)
< _$ invert [Q0] , (λ f {x} → f {suc x}) >
(P? (invert [Q0]) ×-dec decFinSubset (Q? ∘ suc) P?)
any? : ∀ {p} {P : Pred (Fin n) p} → Decidable P → Dec (∃ P)
any? {zero} {P = _} P? = no λ { (() , _) }
any? {suc n} {P = P} P? = Dec.map ⊎⇔∃ (P? zero ⊎-dec any? (P? ∘ suc))
all? : ∀ {p} {P : Pred (Fin n) p} → Decidable P → Dec (∀ f → P f)
all? P? = map′ (λ ∀p f → ∀p tt) (λ ∀p {x} _ → ∀p x)
(decFinSubset U? (λ {f} _ → P? f))
private
-- A nice computational property of `all?`:
-- The boolean component of the result is exactly the
-- obvious fold of boolean tests (`foldr _∧_ true`).
note : ∀ {p} {P : Pred (Fin 3) p} (P? : Decidable P) →
∃ λ z → Dec.does (all? P?) ≡ z
note P? = Dec.does (P? 0F) ∧ Dec.does (P? 1F) ∧ Dec.does (P? 2F) ∧ true
, refl
-- If a decidable predicate P over a finite set is sometimes false,
-- then we can find the smallest value for which this is the case.
¬∀⟶∃¬-smallest : ∀ n {p} (P : Pred (Fin n) p) → Decidable P →
¬ (∀ i → P i) → ∃ λ i → ¬ P i × ((j : Fin′ i) → P (inject j))
¬∀⟶∃¬-smallest zero P P? ¬∀P = contradiction (λ()) ¬∀P
¬∀⟶∃¬-smallest (suc n) P P? ¬∀P with P? zero
... | false because [¬P₀] = (zero , invert [¬P₀] , λ ())
... | true because [P₀] = map suc (map id (∀-cons (invert [P₀])))
(¬∀⟶∃¬-smallest n (P ∘ suc) (P? ∘ suc) (¬∀P ∘ (∀-cons (invert [P₀]))))
-- When P is a decidable predicate over a finite set the following
-- lemma can be proved.
¬∀⟶∃¬ : ∀ n {p} (P : Pred (Fin n) p) → Decidable P →
¬ (∀ i → P i) → (∃ λ i → ¬ P i)
¬∀⟶∃¬ n P P? ¬P = map id proj₁ (¬∀⟶∃¬-smallest n P P? ¬P)
------------------------------------------------------------------------